2020
DOI: 10.2147/cia.s257127
|View full text |Cite
|
Sign up to set email alerts
|

<p>Postoperative Physical Therapy to Prevent Hospital-acquired Pneumonia in Patients Over 80 Years Undergoing Hip Fracture Surgery—A Quasi-experimental Study</p>

Abstract: Background Hip fracture requiring surgical fixation is a common condition with high mortality and morbidity in the geriatric population. The patients are usually frail, and vulnerable to postoperative complications and delayed recovery. Few studies have investigated physical therapy methods to prevent hospital-acquired pneumonia (HAP) after hip fracture surgery. Objective To explore whether an intensified physical therapy regimen can prevent HAP and reduce hospital leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
(65 reference statements)
0
9
0
2
Order By: Relevance
“…One year after hip fracture surgery, one-third of patients do not regain their pre-injury ambulation status or their level of functioning in activi- [ 10 , 11 ]. Moreover, in the search for solutions for more effective prevention protocols to decrease the incidence of postoperative pneumonia, several studies have shown beneficial effects of an oral hygiene protocol [10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…One year after hip fracture surgery, one-third of patients do not regain their pre-injury ambulation status or their level of functioning in activi- [ 10 , 11 ]. Moreover, in the search for solutions for more effective prevention protocols to decrease the incidence of postoperative pneumonia, several studies have shown beneficial effects of an oral hygiene protocol [10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…According to Stahl and Westerdahl, people over 80 may benefit from more intensive physiotherapy after a hip fracture is surgically repaired. Intensive physiotherapy can be given in terms of early mobilization, strengthening of lower limbs, bedside exercises, and breathing exercises [12].…”
Section: Discussionmentioning
confidence: 99%
“…They noted that, compared to the standard population, patients with a geriatric hip fracture demonstrated a functional decline generally 3 times faster than those of the control population. Prior studies have demonstrated the role that post-operative mobilization has on patient outcomes, such as that the inability to mobilize is associated with increased rates of pneumonia and hospital length of stay, 22 and is a key measure in the ability to recover functional independence and the patient's prior level of function. [23][24][25][26][27][28][29] Previous data from our institution demonstrated that ambulating greater than 5 feet within 72 hours was associated with a significantly decreased rate of post-operative morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%